DEVELOPMENT OF STUDENT DISCIPLINE CULTURE IN THE IMPLEMENTATION OF THE SCHOOL'S VISION AND MISSION AT ISLAM JUNIOR HIGH SCHOOL (MTS NEGERI) TAKALAR - Asrullah, Muhammad; Palangkey, Rahmi Dewanti; Bakri, Muhammad Ali; Malli, Rusli (JICSA : Journal of Islamic Civilization in Southeast Asian, 2024)
This study discusses the Development of Discipline Culture of each Student in an effort to improve discipline. Likewise, what happened at Islam Junior High School (MTs Negeri) Takalar. Where the Implementation of Vision and Mission Becomes a benchmark for achieving disciplined Students. This study is a descriptive Qualitative study, Data collection instruments are observation, interviews and documentation, Informants in this study were the head of the madrasah, deputy head of the madrasah, homeroom teachers, and subject teachers, Students. The results of the study showed that the Culture of Discipline at Islam Junior High School (MTs Negeri) Takalar is a school culture based on Islamic culture, which prioritizes emotional spiritual development and strict discipline without neglecting intellectual development. The level of discipline of students at Islam Junior High School (MTs Negeri) Takalar is quite good, several discipline factors, based on observations and data obtained, students show a fairly good level of discipline in terms of time discipline, dress discipline, discipline in class, and discipline in school activities. The impact of implementing the school's vision and mission in developing a culture of discipline at Islam Junior High School (MTs Negeri) Takalar is that the school applies a disciplined attitude to students, both directly and indirectly and consciously, where the school culture that is applied is in accordance with the vision and mission that have been prepared by the school.